Dual triggering for final oocyte maturation. A narrative review - Riobó, Adriana; Martínez Acosta, Andrea; Martinez-Rocca, Lorena; Taboas, Esther; López de Uralde, Belén; Fernandez, Iria; Garrido, Nicolás; Muñoz, Elkin (Frontiers in Endocrinology, 2025)
The dual triggering combines human chorionic gonadotropin (hCG) with GnRH agonists (aGnRH) to induce the final oocyte maturation in in vitro fertilization (IVF). When both drugs are used sequentially, it is called “double trigger”, but this strategy is rarely used clinically. This review explores the rationale for using dual triggering and compares its reproductive outcome with conventional hCG triggering. Variability in protocols, inclusion criteria, study aims, and weak study designs complicate the evaluation of its clinical benefit. Patients with low response or cycles with high proportion of immature oocytes (>25%) may benefit from dual triggering. In contrast, patients with normal or hyper responsiveness show no significant differences compared to conventional hCG triggering. Further robust studies are needed to clarify the clinical applications of dual triggering. Until then, this strategy should remain part of research protocols rather than routine clinical practice.